ASSESSMENT OF HEAVY METAL CONCENTRATION IN VEGETABLES DRIED ALONG FUNTUA-DANJA HIGHWAY KATSINA STATE, NIGERIA - Kankara, U. M.; Nasiru, Rabiu; Garba, Nuraddeen Nasiru; Kankara, Jamila Musa; Kankara, Umar Musa (FUDMA Journal of Sciences, 2021)
One of the major routes of heavy metal exposure to humans is via the consumption of vegetable. The study assessed the contribution of automobile emission on the concentration levels of heavy metals in some of commonly consumed vegetables in Katsina state, Nigeria using Atomic Absorption Spectrometry (AAS). Fresh and dried samples of five (5) commonly consumed vegetables were obtained from Danja-Funtua highway road, 0.5 g of each sample was measured into a clean dried beaker and 10 ml of acidic mixture of HNO3/HClO4 in ratio 2:1 was added to the sample for digestion. The heavy metals concentration in this study ranges from 0.6 – 75.5mg/kg, 0.31 – 1.2mg/kg 278 – 1470mg/kg, 0.4 – 36.3mg/kg and 28 – 65 mg/kg for Pb, Cd, Fe, Ni and Cu respectively. Levels of heavy metals were all found to be above the acceptable limits indicating that inhabitants are at risk of heavy metal contamination
Keywords: heavy metals, vegetable, concentration level, AAS